ANALISIS TINDAK TUTUR ILOKUSI DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA BUYA HAMKA DAN PEMANFAATANNYA BAGI PEMBELAJARAN APRESIASI SASTRA DI SMP - Rio Irawan Saputra (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
This study aims to describe the phenomenon of speech acts on the type of illocution in the novel by Buya Hamka entitled The Sinking of the 2013 Van Der Wijck Ship published by Balai Pustaka. The method used in this research is a descriptive-analytical method by classifying dialogues in the novel that relates to the functions and categories of illocutionary speech acts. Based on the analysis, it was found that; (1) in terms of function, found illocutionary types asking, pleasing, offering, inviting/inviting, cooperating; (2) in terms of categories, assertive, directive, expressive and declaration types are found; (3) in terms of the intensity of the use of illocution, it was found the type of illocution working together as many as 17 utterances; contradict (scold) as many as 12 utterances; assertive as many as 15 utterances. This research can be used as material for learning Indonesian in literary appreciation material for junior high school students.